Understanding India, globalisation and health care systems: a mapping of research in the social sciences - Bisht Ramila; Pitchforth Emma; Murray Susan F (BMC, 2012)
Abstract National and transnational health care systems are rapidly evolving with current processes of globalisation. What is the contribution of the social sciences to an understanding of this field? A structured scoping exercise was conducted to identify relevant literature using the lens of India - a 'rising power' with a rapidly expanding healthcare economy. A five step search and analysis method was employed in order to capture as wide a range of material as possible. Documents published in English that met criteria for a social science contribution were included for review. Via electronic bibliographic databases, websites and hand searches conducted in India, 113 relevant articles, books and reports were identified. These were classified according to topic area, publication date, disciplinary perspective, genre, and theoretical and methodological approaches. Topic areas were identified initially through an inductive approach, then rationalised into seven broad themes. Transnational consumption of health services; the transnational healthcare workforce; the production, consumption and trade in specific health-related commodities, and transnational diffusion of ideas and knowledge have all received attention from social scientists in work related to India. Other themes with smaller volumes of work include new global health governance issues and structures; transnational delivery of health services and the transnational movement of capital. Thirteen disciplines were found represented in our review, with social policy being a clear leader, followed by economics and management studies. Overall this survey of India-related work suggests a young and expanding literature, although hampered by inadequacies in global comparative data, and by difficulties in accessing commercially sensitive information. The field would benefit from further cross-fertilisation between disciplines and greater application of explanatory theory. Literatures around stem cell research and health related commodities provide some excellent examples of illuminating social science. Future research agendas on health systems issues need to include innovative empirical work that captures the dynamics of transnational processes and that links macro-level change to fine-grained observations of social life.